Early detection of impaired glucose tolerance in young adults - May, Khin Soe; Mohd Noor, Noriah; Htite, Lwin Mar; Mohamad Syakirin, Ahmad Syakirin; Mohd Noor Zaidi, Muhammad Ridzuan (2013)
Prevalence of diabetes is on the increase up to 20.8% in adults 18 years old and above as reported by Diabetes Registry Malaysia. There is 5.9% increase as compared to that previous record in 2006. Hence, early detection of impaired glucose tolerance is crucial in prevention of delaying the development of type 2 diabetes mellitus. The study is aimed to determine the relationship of early onset of impaired glucose tolerance and family history of diabetes mellitus. Ninety nine pharmacy students from International Islamic University Malaysia, age range 20-23 years old were recruited. The research was approved by the University’s ethical committee. The students signed the consent form prior to the study. The subject’s biodata which included family history of diabetes mellitus were recorded. Their heights, weight, BMI, blood pressure were recorded and the subjects’ biochemical parameter such as oral glucose tolerance test was investigated. Data was analyzed by SPSS. Fifty nine were female and 40 were male. Sixty seven have family history of diabetes mellitus. The mean value of BMI and fat percentage in female are 22.03 ± 4.02 kg/ M2 and 25.76 ± 4.82%, while the mean value of BMI and fat percentage in male are 23.36 ±4.16 kg/ M2; 16.58 ± 4.99% respectively. Their mean blood sugar level was 4.42 ± 0.35 mmol/L at fasting, 7.7 ±1.49mmol/L at I hour after drinking oral glucose solution and 2hr post challenge test (2HPC) result was 5.98 ± 0.99 mmol/L. 1 HPC of eight subjects were found to be 10 mmol/L and above. Moreover, 2HPC results of 4 of them were also found higher than 7.8mmol/L. This implies that 1 HPC positively correlated with an existing family history of diabetes of mellitus (p<0.016). The findings revealed positive correlation in between family history and impaired glucose tolerance.